A Teachable Moment. - DUNCAN COLLUM, DANNY (Sojourners Magazine)
The article discusses educational-industrial complex and the rising fear of economic domination by better-educated populations. It states that institutions such as textbook publishers, software developers and for-profit schools have vested interest in education policy. Topics include teacher's statement on students' performance called the Student Learning Outcome (SLO), importance of liberal arts education and transformed intellect of black men. Richard Wright's book "Black Boy" is mentioned.